2017
DOI: 10.1002/bmc.3936
|View full text |Cite
|
Sign up to set email alerts
|

Liquid chromatography high resolution mass spectrometry for the determination of baclofen and its metabolites in plasma: Application to therapeutic drug monitoring

Abstract: Baclofen is used to manage alcohol dependence. This study describes a simple method using liquid chromatography coupled to high-resolution mass spectrometry (LC-HR-MS) developed in plasma samples. This method was optimized to allow quantification of baclofen and determination of metabolic ratio of its metabolites, an oxidative deaminated metabolite of baclofen (M1) and its glucuronide form (M2). The LC-HR-MS method on Exactive® apparatus is a newly developed method with all the advantages of high resolution in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Maternal and newborn baclofen and creatinine plasma levels were measured in blood samples at H0 of life (umbilical cord vein), H11, H31, and H102. Creatinine levels were determined using enzymatic reaction, and baclofen concentrations were measured with an in-house validated method [6]. Plasma baclofen concentration of the mother 9 h before delivery was 280 ng/mL (2.5 h after dose intake), and concentrations of the neonate were 205, 105, 24, and below 10 ng/mL (the lower limit of quantification, LLOQ), at H0, H11, H31, and H102, respectively (shown in Fig.…”
Section: Case Report/case Presentationmentioning
confidence: 99%
“…Maternal and newborn baclofen and creatinine plasma levels were measured in blood samples at H0 of life (umbilical cord vein), H11, H31, and H102. Creatinine levels were determined using enzymatic reaction, and baclofen concentrations were measured with an in-house validated method [6]. Plasma baclofen concentration of the mother 9 h before delivery was 280 ng/mL (2.5 h after dose intake), and concentrations of the neonate were 205, 105, 24, and below 10 ng/mL (the lower limit of quantification, LLOQ), at H0, H11, H31, and H102, respectively (shown in Fig.…”
Section: Case Report/case Presentationmentioning
confidence: 99%
“…Beside the different methods of the Pharmacopoeias, several methods for the content determination of baclofen are reported in the literature [13][14][15]. However, methods for impurity profiling of baclofen are quite rare.…”
Section: Introductionmentioning
confidence: 99%
“…A and imp. B [16]. Elagawany et al described a TLC method for the determination of at least two baclofen impurities [17], which can be considered as outdated, because of the typically low sensitivity of TLC.…”
Section: Introductionmentioning
confidence: 99%
“…Thorough literature survey revealed that chromatographic methods, mainly HPLC, are the mostly used methods for BAC analysis. Such as, HPLC with UV detection [2], determination in human plasma by HPLC with several detection methods including tandem mass spectrometry (MS-MS) [3, 4], high-resolution mass spectrometry (HR-MS) [5] and fluorescence detection [6, 7]. In addition, ultra-performance liquid chromatography coupled with MS-MS detection has been used for detecting BAC in blood samples [8].…”
Section: Introductionmentioning
confidence: 99%